Clinical efficacy and safety of high dose trivalent influenza vaccine in adults and immunosuppressed populations – A systematic review and meta-analysis. Issue 4 (October 2021) - Leibovici Weissman, Yaara; Cooper, Lisa; Sternbach, Neta; Ashkenazi-Hoffnung, Liat; Yahav, Dafna
Highlights: We performed a meta-analysis of 16 randomised controlled trials. All trials compared high dose influenza vaccine vs. standard dose. Outcomes suggest high dose vaccine lowers rates of laboratory confirmed influenza. Better serological response was also demonstrated with high dose vaccine. Serious adverse events were significantly less common with high dose vaccine. Abstract: Objectives: Influenza is associated with significant morbidity and mortality, especially in older and immunocompromised patients. Few data are available on the clinical benefit of high dose trivalent influenza vaccine (TIV). We aimed to assess the clinical efficacy and safety of high dose TIV. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs), evaluating high dose versus standard dose TIV for prevention of seasonal influenza in adult population. Primary outcome was laboratory-confirmed influenza. Subgroups analyses included older adults and immunocompromised patients. Results: We included 16 trials, 47, 857 patients; 10 included older adults and three immunocompromised patients. Laboratory confirmed influenza was significantly reduced with high dose TIV (relative risk 0.76, 95% confidence interval 0.64 to 0.9). This outcome stemmed mainly from one trial in older adults. Specifically, A(H3N2) laboratory confirmed influenza, but not A(H1N1) or B lineages, was reduced. No difference in mortality or hospitalizations was demonstrated. Immunological response was significantly higher with high dose vaccine. Serious adverse events were significantly less common in the high dose group. Conclusions: High dose TIV lowers the rates of laboratory confirmed influenza, mainly A (H3N2), in older adults vs. standard dose. Further studies should address immunocompromised patients and report clinical outcomes.